2022
DOI: 10.1002/1873-3468.14458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, metabolic and immunological features of cancers with NRF2 addiction

Abstract: Nuclear factor erythroid‐derived 2‐like 2 (NRF2) is a master transcription factor that coordinately regulates the expression of many cytoprotective genes and plays a central role in defense mechanisms against oxidative and electrophilic insults. Although increased NRF2 activity is principally beneficial for our health, NRF2 activation in cancer cells is detrimental. Many human cancers exhibit persistent NRF2 activation and such cancer cells rely on NRF2 for most of their malignant characteristics, such as ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 109 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…1 B and C). Consistent with this idea, a recent analysis by Kitamura et al revealed NRF2-activated LUSC tumours to be enriched in M2 macrophages, which are differentiated immune cells that are derived from monocytes [ 33 ]. These data from human tumours strongly suggest that NRF2-dependent recruitment of monocytes can play an important role during NRF2-dependent tumorigenesis.…”
Section: Resultsmentioning
confidence: 85%
“…1 B and C). Consistent with this idea, a recent analysis by Kitamura et al revealed NRF2-activated LUSC tumours to be enriched in M2 macrophages, which are differentiated immune cells that are derived from monocytes [ 33 ]. These data from human tumours strongly suggest that NRF2-dependent recruitment of monocytes can play an important role during NRF2-dependent tumorigenesis.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, we now know that Nrf2 is widely recognized as an oxidative stress regulator, but numerous studies have shown that Nrf2 also has an essential role in cancer cell metabolism [55]. Activation of Nrf2 can participate in cancer cell metabolic processes and regulate multiple metabolism related key target genes, such as the production of NADPH, including the main enzymes catalyzing NADPH synthesis: G6PD, IDH1/IDH2, ME1, and PGD, as well as the regulation of the pentose phosphate pathway (PPP), and involved in the regulation of genes involved in glutathione metabolism and glutamine metabolism, among others [56,57]. According to Chio et al, combined targeting inhibition of Akt signaling and synthesis of glutathione could mimic Nrf2 ablation and effectively inhibit the survival of pancreatic ductal adenocarcinoma cells (PDACs) in vitro and in vivo [58].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sirtuin, including the SIRT1-SIRT3 axis, a kind of NAD + -consuming enzyme regarded as a stress responder, has been demonstrated to trigger metabolic reconstitution and affects the ROS level by deacetylating and activating metabolic enzymes and signaling molecules such as FOXO3a, PGC-1α, TFAM, Drp1, mTOR, and PINK1/Parkin [ 35 , 36 , 37 ]. In addition, ROS can activate NF-κB [ 38 ], NRF2 [ 38 , 39 ], and KHK-A [ 40 ] to reduce ROS production. Furthermore, ROS can directly regulate the function of metabolic enzymes through redox modification, which has been demonstrated in key redox-sensitive residues such as cysteine oxidation/S-sulfenylation/S-glutathionylation/S-nitrosylation and tyrosine nitration [ 4 ].…”
Section: Oxidative Stress and Tumor Metabolismmentioning
confidence: 99%